2004
DOI: 10.1063/1.1738639
|View full text |Cite
|
Sign up to set email alerts
|

Glassy phases in random heteropolymers with correlated sequences

Abstract: We develop an analytic approach for the study of lattice heteropolymers and apply it to copolymers with correlated Markovian sequences. According to our analysis, heteropolymers present three different dense phases depending upon the temperature, the nature of the monomer interactions, and the sequence correlations: (i) a liquid phase, (ii) a "soft glass" phase, and (iii) a "frozen glass" phase. The presence of the intermediate "soft glass" phase is predicted, for instance, in the case of polyampholytes with s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
(150 reference statements)
0
13
0
Order By: Relevance
“…As observed in the previous section, we thus obtain a nativelike state which does not correspond to a well-defined secondary structure, but rather to a variety of structures. 40,41 Let us also compare our results with two other recent works on similar models, which conversely take into account excluded volume. 5,7,[37][38][39] Even in this case, the low temperature glasslike phase does not correspond to a fixed structure, but the usual claim is that it would be able to describe average RNA properties.…”
Section: Discussionmentioning
confidence: 66%
“…As observed in the previous section, we thus obtain a nativelike state which does not correspond to a well-defined secondary structure, but rather to a variety of structures. 40,41 Let us also compare our results with two other recent works on similar models, which conversely take into account excluded volume. 5,7,[37][38][39] Even in this case, the low temperature glasslike phase does not correspond to a fixed structure, but the usual claim is that it would be able to describe average RNA properties.…”
Section: Discussionmentioning
confidence: 66%
“…This may be indeed a reason for our qualitatively different results. In order to investigate this issue in more detail, it would be interesting to extend the Bethe lattice analysis to the case of a random heterogeneous sequence, making use the recently proposed cavity method [31], along the lines traced by Montanari, Müller, and Mezard, for the selfavoiding heteropolymer [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…If the phase transition is continuous the density on the coexistence line vanishes. Studies of interacting heteropolymers have confirmed this statement [40,41]. We shall therefore develop a formalism allowing to compute the average density of monomers on a point, ψ, as function of the inverse temperature β, the chemical potential µ and the amount of disorder ρ.…”
Section: Analytic Approach: Polymer In Random Mediamentioning
confidence: 87%
“…The polymer problem can be studied using the cavity method as developed in [40,41]. Here, we shall use only the replica symmetric cavity method as we have not found any evidence for sizeable replica symmetry breaking effects.…”
Section: Analytic Approach: Polymer In Random Mediamentioning
confidence: 99%